Комбатантська проза в сучасній українській літературі: жанрові та художні особливості - Рябченко, М.М. (Слово і Час, 2019)
Упродовж останніх років в українському літературному просторі з'явилася велика кількість
різножанрових текстів, що звертаються до опису сучасних воєнних дій на Сході країни. Серед
авторів цих творів кількісно переважають ті, які до війни не мали письменницького досвіду.
Вони передусім звертаються до самоописових наративів, що їх можна класифікувати як еґо-
документи (щоденники, спогади) та еґо-тексти (автобіографічна художня проза та есеїстика).
У статті проаналізовані жанрові та художні особливості комбатантської прози, наголошено на
відмінності сучасної воєнної літератури від радянської лейтенантської прози, запропоновано
визначення комбатантської прози. During the last few years a significant number of texts covering a huge range of genres appeared
within the Ukrainian literary community with a purpose to depict the recent events of the war taking
place in the East of the country. The most complete list of such literary texts created by Anna Skorina
has more than 400 positions. It includes poetry, fiction, essays, diaries, non-fiction (documentaries and
political researches), photo albums and, surprisingly, comic books and a graphic novel. Moreover, the
list is permanently updated. There are both civilians (writers, journalists, volunteers) and combatants
among the authors of the texts. The prose written by the latter group of authors is an important and
interesting phenomenon of the modern Ukrainian literary process. The group includes professional
writers conscripted into Ukrainian Armed Forces or enlisted in the Volunteer Batallions as well as
authors without pre-war experience of being related to the literary beau monde. To a certain extent
their texts belong to documentaries or to the literature of fact. Most authors resort to self-descriptive
writing for comprehending their recent experience and psychological changes it caused. These works
can be classified as ego-documents (diaries, memoires) and ego-texts (autobiographical fiction
and essays). Genre diffusion is a characteristic feature of memoires and autobiographical prose,
the combatant prose being no exception. Such popular fiction genres as comic books and graphic
novels must be considered a rather interesting practice within modern military literature. The paper
emphasizes the incorrectness of identifying modern combatant prose with so-called lieutenant prose,
the Soviet literary phenomenon, as these groups of texts have essential differences that exceed by
far their common features.